Clinical Profile, Risk Factors and Outcome of the Patient with Cerebral Venous Sinus Thrombosis at 3 Months: Prospective Cohort Study in a Tertiary Care Hospital (Journal of Dhaka Medical College, 2025)
Background: Cerebral venous sinus thrombosis (CVST) one of the important type of venous stroke. With the advent of the newer imaging technique, it is now increasingly diagnosed in our country. There are limited studies regarding venous stroke specially about its outcome in Bangladesh. So, we conducted the study to observe the clinical profile, risk factors and outcome of the patient with cerebral venous sinus thrombosis at 3-month in a tertiary care hospital.Methods: This Prospective cohort study was carried out in the Department of Neurology, Dhaka Medical College Hospital during January 2022 to December 2023. The patients suffering from cerebral venous sinus thrombosis confirmed by imaging were included in this study. The outcome was assessed with mRS score.Results: We included 58 patients with venous stroke, among them about 2/3rd were female. The mean age (SD) of the was 36.46(13.56). Most of the patients were between 20 and 40 years.The most common clinical presentations were headache 54(93%), vomiting 36(62%) and seizure 21 (36.2%). The focal neurologic deficit was present in 17(29%) and papilledema in 33(56.89%) of the patients. The risk factors for CVST identified in the study included CNS infections 22 (41%), then pregnancy and puerperium 8(62%), intake of OCP and other hormonal preparation 6(90%), COVID -19 infection and post vaccination (6.90%), and idiopathic 34(48%). D-dimer was elevated in half of the patients. The commonest sinuses involve were transverse sinus 31(65.51%), and superior sagittal sinus 13 (43.10%). Multiple sinuses involvement was present in more than 2/3rd cases. The mean (SD)hospital stay was 12.4 (3.8) days. At 3-month 44(76%) had mRS 2 score and only 10% patient died. Mortality was higher among males, who had multiple sinus involvement and multiple comorbid conditions.Conclusion: CVST largely affect the young female, mostly present with headache vomiting and seizure. Generally, the outcome is good with conventional treatment.J Dhaka Med Coll. 2024; 33(2) : 56-62